A Precharge-Absorbed DPL Logic for Reducing Early Propagation Effects on FPGA Implementations - He, Wei; de la Torre, Eduardo; Riesgo, Teresa (2011 International Conference on Reconfigurable Computing and FPGAs, 2011)
In this paper, a new countermeasure against power and electromagnetic (EM) Side Channel Attacks (SCA) on FPGA implemented cryptographic algorithms is proposed. This structure mainly focuses on a critical vulnerability, Early Evaluation, also known as Early Propagation Effect (EPE), which exists in most conventional SCA-hardened DPL (Dual-rail with Precharge Logic) solutions. The main merit of this proposal is that the EPE can be effectively prevented by using a synchronized non regular precharge network, which maintains identical routing between the original and mirror parts, where costs and design complexity compared with previous EPE-resistant countermeasures are reduced, while security level is not sacrificed. Another advantage for our Precharge Absorbed(PA) - DPL method is that its Dual-Core style (independent architecture for true and false parts) could be generated using partial reconfiguration. This helps to get a dynamic security protection with better energy planning. That means system only keeps the true part which fulfills the normal en/decryption task in low security level, and reconfigures the false parts once high security level is required. A relatively limited clock speed is a compromise, since signal propagation is restricted to a portion of the clock period. In this paper, we explain the principles of PA-DPL and provide the guidelines to design this structure. We experimentally validate our methods in a minimized AES co-processor on Xilinx Virtex-5 board using electromagnetic (EM) attacks.